Investigação espectroscópica e estudo do mecanismo de conversão descendente de energia em vidros TeO2-WO3 co-dopados com íons Nd3+ E Yb3+ - Costa, Francine Bettio [UNESP] (2016)
The demand for new and renewable energy sources has been of great appeal due to the reduction of environmental impacts. This interest has motivated the research and the development of more efficient and less expensive photovoltaic (PV) cells. Thus, the photovoltaic solar energy has been an option to complement and expand the generation of electricity. However, commercialized crystalline silicon cells present low conversion efficiency of the light irradiation energy into electric energy, mainly due to the spectral mismatch between the regions of maximum solar emission (visible spectrum) and of maximum PV cell efficiency, which is in infrared region. To minimize such losses and, consequently, improve the efficiency of PV cell, down-converters with rare-earth ions in their structure are used to convert the high energy photons (at the visible - Vis) into low energy photons (at the infrared - IR). Meanwhile, in the present work we study the spectroscopic properties of neodymium (Nd3+) and ytterbium (Yb3+) ions incorporated as dopants in a tellurite-tungsten (TW) glass matrix. The characterization of the samples were obtained from measurements of X-ray diffraction, mass density, Fourier transform infrared spectroscopy, Raman spectroscopy, optical absorption, luminescence, excitation, temporal evolution of the luminescence and thermal lens. This study was divided into two stages. Primarily, Nd3+-doped TW glasses were prepared in different atmospheres, i.e., an ambient atmosphere and in another rich in O2 to investigate the influence of the hydroxyl (OH) groups in the spectroscopic properties of samples with different concentrations of Nd3+. The results showed that the energy transfer from Nd3+ ion to the OH group was negligible. The concentration dependency indicated that the energy transference from the Nd3+ ion to the OH group was negligible. In addition, the luminescent quantum efficiency of 4F3/2 level decreased with increasing of Nd3+ concentration. Subsequently, Nd3+ and Yb3+ co-doped TW glasses were prepared in ambient atmosphere to investigate the correlation between Yb3+ ions and down-conversion (DC) mechanisms. The results showed that the luminescence of the 4F3/2 decreased as the concentration of Yb3+ was increased. Simultaneously, it was observed a corresponding increase in the emission of the Yb3+ and a reduction in the generated heat by the sample. The Nd3+ → Yb3+ energy transfer was observed qualitatively and the efficiency of such transfer was quantitatively evaluated by lifetime values. The results indicate that the co-doped TW glasses by Nd3+ and Yb3+ are systems with potential to be used as down-converter material applied to the c-Si photovoltaics cells.